1997
DOI: 10.1093/ndt/12.4.724
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy and ambulatory blood pressure monitoring in chronic renal failure

Abstract: Twenty-four hour ambulatory BP recording and echocardiography are required for accurate diagnosis of inadequate BP control and early LVH in patients with chronic renal impairment, independent determinants of which are hypertension, male sex, BMI, and anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
54
3
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 3 publications
10
54
3
2
Order By: Relevance
“…Some data suggest that mean 24-hour blood pressure is a better predictor of increased LVM than office blood pressure in adults with CRI. 23 In contrast to the CRI group, we were able to show strong relationships of both LVEDD (preload) and indexed SBP or DBP (afterload) to LVM index in the group undergoing dialysis. These results are not surprising, because most of the dialysis children were hypertensive and were undergoing chronic hemodialysis, with two thirds of them having a-v shunting as a result of their graft.…”
Section: Mechanisms Of Increased Lvm In Children With Chronic Renal Dcontrasting
confidence: 67%
“…Some data suggest that mean 24-hour blood pressure is a better predictor of increased LVM than office blood pressure in adults with CRI. 23 In contrast to the CRI group, we were able to show strong relationships of both LVEDD (preload) and indexed SBP or DBP (afterload) to LVM index in the group undergoing dialysis. These results are not surprising, because most of the dialysis children were hypertensive and were undergoing chronic hemodialysis, with two thirds of them having a-v shunting as a result of their graft.…”
Section: Mechanisms Of Increased Lvm In Children With Chronic Renal Dcontrasting
confidence: 67%
“…This is true for markers of kidney damage, such as proteinuria, wherein a cross-sectional study of 232 CKD patients found ABPM is more strongly associated with proteinuria than was clinic BP. 17 ABPM is also more strongly associated with echocardiographic left ventricular hypertrophy than is clinic BP, as shown in studies of disparate CKD populations such as (i) a study of 85 CKD patients without diabetes or history of cardiovascular disease, 18 (ii) in a study of 26 normotensive patients with polycystic kidney disease, 19 (iii) and in 599 CKD patients from the AASK cohort study. 20 …”
Section: End Organ Damagementioning
confidence: 92%
“…Ambulatory blood pressure monitoring (ABPM) may be more informative about the severity of BP elevation than clinic measurements in renal failure and following renal transplantation. 9,10 Additionally, the possibility of noninvasive measurement of BP at night and during sleep by ambulatory monitoring devices has stimulated interest in the pathophysiological significance of night-time BP. Blood pressure at night was reported to be independently associated with end-organ damage above the risk associated with daytime values.…”
Section: Introductionmentioning
confidence: 99%